Mobility, transport and carbon - Givoni, M; Banister, D (Edward Elgar, 2013)
The wheel first came into use about 6000 years ago and since then it has been one of the most influential and useful inventions. Most personal movement is totally dependent on the wheel in some form or other, and it is an essential part of the ever moving world. Society is also reliant on the movements of other people and/or goods, and those movements taken together very much explain and define our society. In the not too distant past ‘feet’ shaped the boundaries of our perceived and experienced world, but now it is the wheel. The movement of people and goods has grown exponentially over the last 50 years, in both spatial scale and importantly in distance, and the world has been ‘shrunk’. This has brought enormous benefits but some formidable challenges as well, some of which we are only now starting to realize, to understand and to act upon. At the heart of the ‘carbon problem of transport’ is the two-way relationship between mobility and transport. These two concepts provide the links between our desire to move, to change our life situation, to fulfil our aspirations and to provide the means available to physically move. While the desire to move shapes our transportation system, it is at the same time shaped by it.